Dissecting the Role of VicK Phosphatase in Aggregation and Biofilm Formation of Streptococcus mutans. (June 2021) - Wang, S.; Long, L.; Yang, X.; Qiu, Y.; Tao, T.; Peng, X.; Li, Y.; Han, A.; Senadheera, D.B.; Downey, J.S.; Goodman, S.D.; Zhou, X.; et al.
VicRK (WalRK or YycFG) is a conserved 2-component regulatory system (TCS) that regulates cell division, cell wall biosynthesis, and homeostasis in low-GC Gram-positive bacteria. VicRK is also associated with biofilm formation of Streptococcus mutans on the tooth surface as it directly regulates the extracellular polysaccharide (EPS) synthesis. Of the 2 components, VicK possesses both autokinase and phosphatase activities, which regulate the phosphorylation and dephosphorylation of the regulator VicR in response to environmental cues. However, the dual mechanism of VicK as the autokinase/phosphatase in regulating S. mutans ' responses is not well elucidated. Previously, it has been shown that the phosphatase activity depends on the PAS domain and residues in the DHp domain of VicK in S. mutans. Specifically, mutating proline at 222 in the PAS domain inhibits VicK phosphatase activity. We generated a VicK P222A mutant to determine the level of VicR-P in the cytoplasm by Phos-tag sodium dodecyl sulfate polyacrylamide gel electrophoresis. We show that in VicK P222A phosphatase, attenuation increased phosphorylated VicR (VicR-P) that downregulated glucosyltransferases, gtfBC, thereby reducing the synthesis of water-insoluble polysaccharides (WIS-EPS) in the biofilm. In addition, VicK P222A presented as long-rod cells, reduced growth, and displayed asymmetrical division. A major adhesin of S. mutans, SpaP was downregulated in VicK P222A, making it unable to agglutinate in saliva. In summary, we have confirmed that VicK phosphatase activity is critical to maintain optimal phosphorylation status of VicR in S. mutans, which is important for cell growth, cell division, EPS synthesis, and bacterial agglutination in saliva. Hence, VicK phosphatase activity may represent a promising target to modulate S. mutans ' pathogenicity.